Effect of managerial ownership on bank value: insights of an emerging economy. Issue 2 (26th August 2020) - Moudud-Ul-Huq, Syed; Biswas, Tanmay; Proshad Dola, Shukla
Abstract : Purpose: This study aims to empirically investigate the effect of managerial ownership on bank value concerning conventional and Islamic bank. The analysis uses a balanced panel data set based on a sample consisting of 480 bank-year observations between 2003 and 2017. Design/methodology/approach: Ordinary least squares, fixed effect and random effect have been used primarily to examine the relationship between managerial ownership and banks' value. Later, the authors validate the core results by using the generalized linear model. Findings: This study provides general support for the claim of interest alignment that encourages bank standards with a high level of managerial ownership and partly opposes the view of the entrenchment effects.In addition, the study finds a U-shaped and insignificant relation between managerial ownership and bank value. This indicates that initially, managerial ownership is a blessing, and later, it becomes a curse in considering bank value. Moreover, bank value affects managerial ownership positively both for conventional and Islamic banks. Originality/value: A good number of studies are available in the current literature, which examine the impact of managerial ownership on either bank performance or risk-taking. However, very few studies are found that examine the bidirectional relationship between managerial ownership and banks' value. Moreover, to the best of authors' knowledge, there is a dearth of literature on this topic that is built on the comparative analysis between conventional and Islamic banks.